ANALISIS KADAR GLUKOSA DARAH PADA PEROKOK AKTIF DI RT 03 DUSUN 02 DESA TEBEDAK II KECAMATAN PAYARAMAN KABUPATEN OGAN ILIR : Indah Hamida (JURNAL SMART ANKes, 2021)
Nicotine content in cigarettes can affect insulin action. Nicotine will enter the blood directly and then will be carried up to the brain. Then nicotine will stimulate the adrenal glands which will increase adrenaline for the body. This relationship causes nicotine to cause the risk of diabetes, especially type 2 diabetes. The purpose of this study was to determine the analysis of blood glucose levels in active smokers in RT 03 Dusun 02 Tebedak Village II, Payaraman District, Ogan Ilir Regency based on age, duration, and type of cigarette. . The design used in this research is descriptive andthe method used is accidental sampling. The blood glucose test method used is the strip method. The results showed that the results of research conducted on 32 samples of active smokers obtained normal blood glucose results as many as 12 people (38%) and blood glucose above normal as many as 20 people (62%). Based on age <40 years, the results were 15 people with normal blood glucose levels as many as 8 people (57%) and above normal as many as 7 people (46%). Meanwhile, for the age of 40 years, the results were 17 people with normal blood glucose levels as many as 5 people (29%) and above normal as many as 12 people (71%). Smoking duration 10 years resulted in 8 people with normal blood glucose levels as many as 4 people (50%) and above normal as many as 4 people (50%), while from smoking duration >10 years, 24 people with high levels of smoking obtained results. normal blood glucose as many as 8 people (33%) and above normal as many as 16 people (67%). Types of filter cigarettes obtained results as many as 16 people with normal blood glucose news 9 people (56%) and above normal 7 people (44%). As for the type of Non-Filter cigarettes, there were 16 results with normal blood glucose levels as many as 3 people (19%) and above normal as many as 13 people (81%).